Systematic Literature Review: Perbandingan Kinerja Algoritma Penjadwalan CPU FCFS, SJF, Round Robin, dan Priority - Abdurrahman Al Ghifari; Herbert Siregar (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Efficient CPU scheduling is essential to reduce waiting time, turnaround time, and maximize throughput. This study conducts a Systematic Literature Review (SLR) to compare FCFS, SJF, RR, and Priority Scheduling based on these metrics (RQ1), and to examine trade-offs between fairness and efficiency across different workload contexts (RQ2). Using the PRISMA method, 7 articles from 2015–2025 were selected from Scopus. Data were synthesized on scheduling performance, and VOSviewer was used for bibliometric mapping. Results show SJF excels in batch environments with lowest waiting (≈15 ms) and turnaround times (≈30 ms). Adaptive RR variants provide high throughput (up to 1200 jobs/s) and low latency in real-time, at a cost of increased context-switch overhead (5–12%). FCFS, although simple, results in high delays. Hybrid algorithms offer a balance between fairness and performance. Bibliometric analysis confirmed dominant research clusters on SJF and RR adaptations.